CYC1 Silencing Sensitizes Osteosarcoma Cells to TRAIL-Induced Apoptosis - Li, Guodong; Fu, Dong; Liang, Wenqing; Fan, Lin; Chen, Kai; Shan, Liancheng; Hu, Shuo; Ma, Xiaojun; Zhou, Ke; Cheng, Biao (Cellular physiology and biochemistry, 2014)
Aims: Osteosarcoma (OS) is an aggressive bone malignancy with poor prognosis. Many OS cells are resistant to apoptotic induction by tumor necrosis factor-related apoptosis inducing ligand (TRAIL). In our previous study, we found that the serum level of cytochrome c1 (CYC1) is significantly higher in OS patients than in healthy subjects. Our aim was to investigate the effects of CYC1 silencing on TRAIL-induced apoptosis in human OS in vitro and in vivo along with the underlying mechanisms. Methods: First, we determined the expression of CYC1 in human OS tumors and cell lines versus normal adjacent tissues and cell line. We then studied the effects of CYC1 silencing alone or in combination with TRAIL on OS cell growth and apoptosis in vitro and OS tumorigenesis in vivo. Results: We found that CYC1 is overexpressed in human OS tissues and cell lines. CYC1 silencing by shRNA transfection inhibits proliferation, slightly induces apoptosis in human OS cells in vitro, and suppresses human OS tumor growth in a mouse xenograft model in vivo. Additionally, CYC1 silencing sensitizes OS to TRAIL-induced apoptosis in vitro and in vivo. Our results also showed that CYC1 silencing significantly reduces complex III activity and potentiates TRAIL-induced cytochrome c release and caspase-9 activation in OS cells, suggesting that CYC1 silencing acts via the mitochondria-dependent apoptotic pathway. Conclusion: Taken together, our results provide evidence that CYC1 plays an important role in OS tumorigenesis, and modulation of CYC1 may be an effective strategy to potentiate OS to apoptotic induction by TRAIL.